Application Of The Field Trip Method To Improve The Ability To Write Descriptions Of Students At SMA Negeri 3 Kab. Wajo - Nur Rahmi; Arisa; Abdul Kadir; Andi Halmina; Putri Wulandari (Universitas Cokroaminoto Palopo, 2023)
This study aims to improve the students writing description skills of class XI through the application of the field trip method located at Senior High School 3 Wajo. This research is Classroom Action Research (CAR), which is aimed to improve the quality of learning practices in the classroom. The collected data were analysed critically by comparing the results of the actions in each cycle. The results obtained from this study include: (1) the application of the field trip method can improve writing learning. This is indicated by the increased activeness, attention, concentration, interest, and motivation of students in learning to write descriptions. (2) the application of the field trip method can improve students' ability to write descriptions. This is indicated by the increasing value of the students' writing. In cycle I the lowest score of students was 59 and the highest score of students was 82, while in cycle II the lowest score of students was 64 and the highest score of students was 95, (3) the completeness of student learning outcomes increased. In the first cycle the completeness of the learning outcomes was only 48% or 12 students and in the second cycle it was 96% or 24 students. The conclusion of this study is that the application of the field trip method can improve students' ability to write descriptions.